Applications scenarios of edge computing - Cao, Jie (IEEE, 2018)
This course introduces the application scenarios of edge computing. Three real-world applications including smart home, public service, and the autonomous vehicle will be covered in this course along with the discussion of the benefits and challenges by employing Edge computing. This course will be instructional for practitioners in their designing and developing of their Edge computing applications
Description based on online resource; title from title screen (IEEE Xplore Digital Library, viewed November 16, 2020)
Keywords: Cloud computing; Software development; Film